FAKTOR-FAKTOR PENYEBAB BERMASALAH KINERJA KARYAWAN - Euis Saribanon; Raden Roro Riri Kurniawati (Institut Transportasi dan Logistik Trisakti, 2015)
Road Transportation Terminal Unit businessis the operational hub terminals in Jakarta. Unit Road Transportation Terminal Unit businesshas a direct responsibility to the Head of Jakarta Transportation Department which is under and directly responsible to the Governor of DKI Jakarta through the secretary. This study was conducted to determine the performance level of employees of Road Transportation Terminal Unit businessin 2013. The study is using the method of fishbone analysis. Analysis and discussion of the results obtained the conclusion that the percentage of main categories for human resources was 55.56%. It stated that the task sequence has not been implemented properly. The percentage of main categories for engine was 58.33%. It stated that the use of an official car to carry out the task of day-today has not been effective yet. Ultimately, the percentage of main categories for motivation was 83.33%. It stated that it is needed to apply a reward and punishmentsystem.